Comparative Analysis Of The 2018 Science Curriculum and the 2024 Türkiye Century Education Model Science Curriculum In Terms of Sustainable Development Themes - Kargalıoğlu, Elif (Research Trends In Educational Sciences, 2025)
The aim of this study is to conduct a comparative analysis of the 2018 Science Curriculum and the 2024 Türkiye Century Education Model Science Curriculum in terms of sustainable development themes. The research employs document analysis, one of the qualitative data collection methods. Within the scope of this method, priority was given to accessing primary data sources to ensure the reliability and accuracy of the examined documents. During the research process, the Science Curricula approved by the Board of Education and Discipline were used as the primary data source, and written as well as visual materials were analyzed. The data were evaluated through content analysis, highlighting the similarities and differences between the curricula. The learning outcomes were also analyzed by the researcher and two experts specializing in science education, yielding an intercoder reliability coefficient of 0.89. Findings reveal that the 2018 Science Curriculum includes 87 learning outcomes related to sustainable development, whereas this number decreases to 53 in the 2024 curriculum. The learning outcomes in the 2018 curriculum are scattered across various topics, while the 2024 curriculum offers a more structured approach to sustainability, allocating more time to these themes and distributing them more evenly. This focused treatment in the 2024 curriculum contributes significantly to the transformation of knowledge and awareness into behavior.